Implementasi Pembelajaran IPS Terpadu Terhadap Pembentukan Karakter Sikap Peduli Lingkungan pada Siswa Kelas VIII MTs Unggulan Rohmatul Ummah Mojokerto - Zarotul Agustin (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research is motivated by the formation of environmentally caring character in students by teaching children to throw away rubbish, love plants or the environment and always maintain cleanliness wherever they are, especially in the school environment. Students are given activities about loving and caring for the environment, even if it's just cleaning the classroom. This research uses a qualitative approach, the research location was carried out at MTs Unggulan Rohmatul Ummah Mojokerto, by optimizing the presence of researchers in extracting data based on sources, namely: (1) primary data sources (2) secondary data sources. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used in this research are data collection, data reduction, data presentation and conclusion drawing, then checking the validity of the data findings using triangulation. The results of this thesis research are (1) The children have succeeded in changing their personalities in the way they interact, in keeping the environment clean, such as throwing rubbish in its place, always carrying out picket duties and inviting their friends to maintain cleanliness (2) Evaluation of the implementation of character education used by the school is carried out every Sunday or if possible every day by the homeroom teachers, teachers and also the principal, and also carried out every semester. In forming a socially caring character through Social Sciences subjects, it is able to change the character of students for the better.